Upstairs, downstairs. The complete series, v. 15-16 [videorecording (DVD)] - Jackson, Gordon, 1923-1990; Baddeley, Angela, 1904-1976; Marsh, Jean; Hawkesworth, John (A & E Television Networks : Distributed by New Video, 2005)
This is the fourth season of the television program Upstairs downstairs. The aristocratic Bellamy family and their servants deal with the changes caused by the First World War.